ANNA M. GADE DAN MTQ DI INDONESIA: SEBUAH KAJIAN METODOLOGIS - Nur Rohman (UIN Raden Mas Said Surakarta, 2016)
This article constitutes to repeatedly reading the orientalist’s research findings on the practice of the holy Qur’an’s reading in Indonesia. It is very important, especially related to the methodology used, because at the same time both of those who are interested to study the holy Qur’an and the cultural observers see the various daily activities of the people showing the natural phenomenon that can be approached through the social-humanities disciplines. This article explained that Anna M. Gade operated Clifford Geertz’s theory on religion as cultural system. Anna Gade said that the practical reading of the Qur’an (in Indonesia) is constituted by several things, which then grouped into motivation and mood.